Optimising T-cell immunotherapy in patients with multiple myeloma: practical considerations from the European Myeloma Network - Donk, Niels van de; Moreau, Philippe; San-Miguel, Jesús F; Mateos, Maria-Victoria; Dimopoulos, Meletios A; Zweegman, Sonja; Gay, Francesca; Engelhardt, Monika; Mina, Roberto; Zamagni, Elena; Delforge, Michel; Beksac, Meral; et al. (The lancet. Haematology, 2025)
Novel T-cell immunotherapies (chimeric antigen receptor [CAR] T cells and T-cell redirecting bispecific antibodies) are changing the treatment landscape of relapsed or refractory multiple myeloma. In this Review, the European Myeloma Network provides recommendations to optimise both safety and efficacy of T-cell immunotherapy. In patients who are eligible for both CAR T-cell therapy and bispecific antibodies, we recommend using CAR T-cell therapy first due to the high response rate and durable progression-free survival, accompanied by improved quality of life. Furthermore, previous bispecific antibody treatment has a negative effect on the efficacy of CAR T-cell therapy, and there is emerging evidence that suggests that relapse after B-cell maturation antigen-directed CAR T-cell therapy can be effectively managed with bispecific antibodies. Timely referral and planning are crucial before initiating T-cell immunotherapy to optimise treatment selection, conduct adequate diagnostic tests (eg, excluding latent infections), and identify modifiable risk factors to improve clinical outcomes. Supportive care is crucial in all patients receiving T-cell immunotherapy to prevent non-relapse mortality.
Online verfügbar: 25. Juni 2025, Artikelversion: 4. August 2025
Gesehen am 22.01.2026